Unveiling the Influence of Non-Toxic Fluorinated Ionic Liquids Aqueous Solutions in the Encapsulation and Stability of Lysozyme - Ferreira, Margarida L. (2022)
Proteins are bioactive compounds with high potential to be applied in the biopharmaceutical industry, food science and as biocatalysts. However, protein stability is very difficult to maintain outside of the native environment, which hinders their applications. Fluorinated ionic liquids (FILs) are a promising family of surface-active ionic liquids (SAILs) that have an amphiphilic behavior and the ability to self-aggregate in aqueous solutions by the formation of colloidal systems. In this work, the protein lysozyme was selected to infer on the influence of FILs in its stability and activity. Then, the cytotoxicity of FILs was determined to evaluate their biocompatibility, concluding that the selected compounds have neglected cytotoxicity. Therefore, UV–visible spectroscopy was used to infer the FIL-lysozyme interactions, concluding that the predominant interaction is the encapsulation of the lysozyme by FILs. The encapsulation efficiency was also tested, which highly depends on the concentration and anion of FIL. Finally, the bioactivity and thermal stability of lysozyme were evaluated, and the encapsulated lysozyme keeps its activity and thermal stability, concluding that FILs can be a potential stabilizer to be used in protein-based delivery systems.